2019
DOI: 10.3389/fpls.2019.01125
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Limitations of Crop Phenotyping in Southern European Countries

Abstract: The Mediterranean climate is characterized by hot dry summers and frequent droughts. Mediterranean crops are frequently subjected to high evapotranspiration demands, soil water deficits, high temperatures, and photo-oxidative stress. These conditions will become more severe due to global warming which poses major challenges to the sustainability of the agricultural sector in Mediterranean countries. Selection of crop varieties adapted to future climatic conditions and more tolerant to extreme climatic events i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 99 publications
(116 reference statements)
0
40
0
Order By: Relevance
“…Overall, the great deal of interest shown in the last decade on thermal imaging is mainly related with its rapidity of determination, non-invasive nature, and robustness. These characteristics makes thermal imaging a promising technique for modern crop phenotyping [16]. Under this context and based on the findings of this study, thermal indicators, such as CWSI, can be a valuable complementary tool for garlic crop management (e.g., soil moisture monitoring, irrigation scheduling, cultivar selection, and yield prediction).…”
Section: Models' Verification and Variable Reliability As Bulb Biomasmentioning
confidence: 75%
See 1 more Smart Citation
“…Overall, the great deal of interest shown in the last decade on thermal imaging is mainly related with its rapidity of determination, non-invasive nature, and robustness. These characteristics makes thermal imaging a promising technique for modern crop phenotyping [16]. Under this context and based on the findings of this study, thermal indicators, such as CWSI, can be a valuable complementary tool for garlic crop management (e.g., soil moisture monitoring, irrigation scheduling, cultivar selection, and yield prediction).…”
Section: Models' Verification and Variable Reliability As Bulb Biomasmentioning
confidence: 75%
“…Thus, intraspecific characterization of functional and yield responses to the environment should be a key approach in crop breeding and selection programs [14]. For this purpose, crop phenotyping and cultivar selection must be performed in a cost-effective manner with practical implementation [15][16][17]. In this sense, the use of new technologies, along with enhanced…”
Section: Introductionmentioning
confidence: 99%
“…This should be also accompanied by the development of extension activities promoted by the local government or local associations. An increased investment in phenotyping tools and network [88], as well as on agricultural extension services, is needed. This is especially true in countries such as Portugal, where crop phenotyping is not organized and the national authorities have substantially reduced their extension activities.…”
Section: Discussionmentioning
confidence: 99%
“…The OJIP transient proved to be very responsive to stress caused by different environmental factors [8][9][10][11][12][13]. Thus, this technique has been extensively used in low throughput plant phenotyping (Costa et al [14] and references therein) to phenotype the physiological status of plants, i.e., to position the phenotype along the "condition or situation axis" of the conceptual phenotype space proposed by the USDA/NSF [15]. However, Tyystjarvi et al [16] suggested that the Kautsky curve is a built-in bar code that can be used in the automatic identification of plant species, when coupled with artificial intelligence techniques.…”
Section: Introductionmentioning
confidence: 99%